Development of the deepwater turbine installation-floating concept - Serret i Magaz, Jordi; Serret, Jordi (The University of Edinburgh, 2020)
Floating offshore wind turbine technology is progressing from the research stages to commercial projects. It will be an increasing source of renewable energy over the next few years. The better quality of the wind resource and environmental considerations will encourage developers further offshore, if commercially viable. This research work presents the initial development of the Deep Turbine Installation-Floating (DTI-F) concept. The DTI-F concept is a hybrid spar buoy-based floating offshore substructure capable of supporting a 7 MW wind turbine with the uniqueness of being able to raise and lower the tower and nacelle, which simplifies construction, installation, maintenance, and de-commissioning. The research proceeds in three parts; the first part is a compilation of the background of floating wind turbines and the DTI-F concept. A novel construction method and the installation and assembly processes are outlined, as well as the parametric approach used to perform the preliminary design of the floater. The second part presents both the aerodynamic and hydrodynamic modelling techniques applied during this research. It covers the aeroelastic analysis of the Levenmouth wind turbine (WT) and the experimental and numerical hydrodynamic analysis of the DTI-F concept holding the Levenmouth WT. The Levenmouth (Samsung Heavy Industries - S7.0-171) offshore wind turbine owned by the Offshore Renewable Energy Catapult (ORE Catapult) is a real, operating demonstration wind turbine. The aeroelastic model of the Levenmouth WT has provided the load-matrix of a real, operating seven megawatts WT. The results of the aeroelastic analysis have been integrated parametrically into the design of the DTI-F floater. The hydrodynamic analysis of the floating system undertaken for this research is based on experimental and numerical modelling work. A 1:45 Froude scale model of the DTI-F wind concept was tested using three different mooring configurations: i) three mooring lines, ii) four mooring lines, and iii) three mooring lines ...